Microfabrication Technologies for Interaction Circuits of THz Vacuum Electronic Devices - Xinghui Li; Jinjun Feng (Micromachines)
Advances in manufacturing technology are allowing for the realization of interaction circuit with microstructures. The capability to produce small circuit structures is allowing new opportunities for vacuum electronic devices producing terahertz (THz) frequency radiation, which is impractical with traditional machining technology. This publication reviews recent progress on advanced microfabrication technologies applicable to interaction circuits of THz vacuum electronic devices, including LIGA/UV-LIGA (Ultraviolet Lithographic, Galvonoformung and Abformung), deep reactive ion etching (DRIE), micro/nano computer numerical control (CNC) milling, three-dimension (3D) printing, etc., and describes the current State-of-the-Art of their applications.